Improved Diagnostic Accuracy of Periprosthetic Breast Infection: Novel Application of the Alpha Defensin-1 Biomarker. Issue 11 (November 2019) - Basta, Marten N.; Liu, Paul Y.; Kwan, Daniel; Breuing, Karl H.; Sullivan, Rachel; Jehle, Charles C.; Bass, Jonathan L.; Zienowicz, Richard J.; Schmidt, Scott
Abstract : Background: Prompt, accurate diagnosis of breast implant infection is critical to minimizing patient morbidity. Bacterial culture false negative rate approaches 25%–30%, and better costeffective testing modalities are needed. Alpha defensin-1 (AD-1) is a neutrophil-mediated biomarker for microbial infection. With sensitivity/specificity of 97% and 96%, it has replaced culture as the preferred diagnostic modality for orthopedic periprosthetic infection, but has yet to be investigated in breast reconstruction. This pilot study compares the diagnostic performance of AD-1 to bacterial culture in suspected periprosthetic breast infection. Methods: Patients with prosthetic breast reconstruction and suspected periprosthetic infection were prospectively studied. Implant pocket fluid was analyzed with gram stain and culture, AD-1 assay, and adjunctive markers. Demographics, operative history, prosthetic characteristics, and antibiotic exposure were collected, and diagnostic performance of each test was compared. Results: Fifteen breasts with suspected periprosthetic breast infection were included, 10 (66.7%) of which were acutely infected. Gram stain correctly identified only 1 of 10 infections, whereas culture failed to identify 1 infection and reported equivocal/false-positives in 2 noninfected samples. AD-1, however, correctly classified all 15 samples. AD-1 exhibited 100% sensitivity and specificity, comparing favorably to culture (sensitivity: 90%, specificity: 60%), although this did not reach significance (P=0.22). Infected breasts also demonstrated significantly higher adjunctive marker levels compared to noninfected breasts. Conclusions: This study demonstrates the utility of AD-1 in diagnosing periprosthetic breast infection. Combining AD-1 with adjunctive inflammatory markers may allow more accurate, prompt detection of implant infection which may reduce morbidity and reconstructive failures.